Associação entre os hábitos alimentares e estilo de vida com o excesso de peso durante a pandemia de COVID-19 - BARROQUEIRO, Ângela Tâmara Souza (2023)
Introduction: The COVID-19 pandemic changed the routine of the population, generating direct impacts on lifestyle, including eating habits favoring overweight. Objective: assess the eating behavior and lifestyle of individuals during the COVID-19 Pandemic. Material and Method: Analytical cross-sectional study, which evaluated 386 adults aged between 19 and 59 years old throughout the Brazilian territory. The research was developed from September to December 2020 using an online platform. The variables studied were: sociodemographic, nutritional status (anthropometry and food consumption); Lifestyle: smoking, alcohol consumption, water consumption, physical activity, sleep quality, descriptive assessment of the form of fecal content. Data were tabulated in Microsoft Office Excel® and analyzed using the statistical program SPSS 21.0®. Results: A total of 386 individuals were evaluated, of which 177 (45.9%) were overweight. In the population studied, women (75.1%), individuals between 20 and 29 years old, white (44.0%), residents of the northeast region (84.7%), with incomplete higher education (49.2%) predominated. Of these, 40.4% were health professionals. At least 12.7% of those evaluated reported some comorbidity, arterial hypertension the most common comorbidity (4,4%), with a greater association (p value < 0.05) for obese individuals (16.4%). No associations were observed between overweight and perception of lifestyle and variation in eating habits. Among obese individuals, at least 27.1% of those evaluated classified this aspect as “Very bad/bad”. The results show a reduction in the number of smokers, alcoholics and practitioners of physical activity when comparing the period before and during the pandemic, especially of people who were not overweight. Most respondents consumed less than 1L of water daily, consumed pasta (47.7%), dairy products (53.4%) more than once a day. In addition, participants reported consuming the following items between 1 and 4 times a week: fruit (39.1%); vegetables (49.5%); sugar (45.9%) and sausages (36.3%). Overweight individuals reported more frequently (p < 0.05) weight gain (72.2%), anxiety (57.6%) and feelings of guilt for bad eating habits (57.1%), than individuals without obesity (56.0%, 42.6% and 39.2%), respectively. Conclusion: there was a decrease in the consumption of fruits and vegetables and an increase in sweets and fast food, revealing changes in the dietary pattern of consumption, important to be reflected in the health of Brazilians. These data point to the need for nutritional and dietary monitoring in Ministry of Health indicators for planning more effective health measures..